2013
DOI: 10.1007/s00418-013-1121-x
|View full text |Cite
|
Sign up to set email alerts
|

Chondrogenic differentiation of human bone marrow-derived mesenchymal stem cells treated by GSK-3 inhibitors

Abstract: A study of the cartilage differentiation of mesenchymal stem cells (MSCs) would be of particular interest since one strategy for cell-based treatment of cartilage defects emphasizes the use of cells that are in a differentiated state. The present study has attempted to evaluate the effects of two well-known glycogen synthase kinase-3 inhibitors, including lithium chloride (LiCl) and SB216763 on a human marrow-derived MSC (hMSC) chondrogenic culture. Passaged-3 MSCs were condensed into small pellets and cultiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 43 publications
3
25
0
Order By: Relevance
“…Arioka et al showed that lithium chloride inhibits GSK-3, one of the main regulators of the Wnt/b-catenin pathway, which plays a crucial role in the differentiation of osteoblasts. In addition, Hui et al [2] demonstrated that lithium can reduce the degradation of collagen via a cytokine-induced pro-inflammatory response in cartilage and Eslaminejad et al [8] showed that lithium enhances the formation of proteoglycan-rich extracellular matrix in chondrogenic culture of mesenchymal stem cells. These findings are of particular interest since cartilage is one of the most challenging tissues to regenerate, since it is avascular.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arioka et al showed that lithium chloride inhibits GSK-3, one of the main regulators of the Wnt/b-catenin pathway, which plays a crucial role in the differentiation of osteoblasts. In addition, Hui et al [2] demonstrated that lithium can reduce the degradation of collagen via a cytokine-induced pro-inflammatory response in cartilage and Eslaminejad et al [8] showed that lithium enhances the formation of proteoglycan-rich extracellular matrix in chondrogenic culture of mesenchymal stem cells. These findings are of particular interest since cartilage is one of the most challenging tissues to regenerate, since it is avascular.…”
Section: Introductionmentioning
confidence: 99%
“…2 Results and discussion 2.1 Effect of the lithium salt on the sol-gel process Eslaminejad et al [5,8] studied the effect of Li þ concentration on mesenchymal stem cells, from 1 to 10 mM. They found 5 mM to be optimal in terms of inducing chondrogenic differentiation of MSCs in a pellet culture system.…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, the stimulatory effects of GSK-3 antagonist on chondrogenic differntiation of human bone marrow derived stromal cells in 3-D micromass/pellet culture have been reported 9,10 . These studies, however, suggested that the interaction between pathways initiated by both TGF-β3 and Li was a prerequisite for the enhanced .…”
Section: Discussionmentioning
confidence: 92%
“…SiO2 -Li2O glass used in the present study was designed to deliver 5 mM of Li. The reason this dose was chosen was that previous studies demonstrated that the effects of lithium on cellular behaviour is dose dependent with optimal cell viability when culture medium contained 5 mM lithium and higher concentration of Li (7 mM) reduced cell viability 9,10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation